Cultural insights into arithmetic sequences: A study of chinese zodiac and its elements - Gusti Ayu Made Arna Putri; Ni Putu Ayu Mirah Mariati; I Ketut Suwija (Journal of Honai Math)
Ethnomathematics examines the intersection of mathematics and cultural practices, revealing how mathematical principles are embedded within societal traditions. Despite extensive research in ethnomathematics, limited studies have explored its application in understanding the Chinese zodiac system and its mathematical foundations. This study addresses this gap by investigating the mathematical structures underlying the determination of the Chinese zodiac and its elements, offering a novel perspective on how arithmetic sequences and modular arithmetic are utilized within this cultural tradition. The study aims to formulate these traditional calculations into a mathematical framework, thereby bridging cultural heritage and mathematical learning. Employing a qualitative research design with an ethnographic approach, data collection was conducted through field observations, in-depth interviews, and thematic analysis to ensure validity, reliability, and representativeness. The findings reveal that the determination of the Chinese zodiac and its elements involves fundamental mathematical operations such as multiplication, addition, and modular arithmetic. This study not only demonstrates the inherent mathematical reasoning within cultural traditions but also contributes to the broader discourse on mathematics education by integrating cultural contexts into learning. Finally, the results have significant implications for mathematics education, offering an alternative pedagogical approach that enhances students’ engagement and comprehension by contextualizing mathematical concepts within real-life cultural practices.